2018
DOI: 10.1109/led.2017.2774604
|View full text |Cite
|
Sign up to set email alerts
|

Cell-to-Cell Fundamental Variability Limits Investigation in OxRRAM Arrays

Abstract: In this paper the fundamental variability limits of filament based OxRRAM are investigated considering different transistor sizes and MIM stacks featuring different materials and thicknesses. Cell-to-cell variability is analyzed through an extensive characterization of Forming, Set and Reset operations on 4kbits OxRRAM arrays. The results obtained in terms of switching voltage variability and resistance variability from cell to cell are compared and discussed to identify the variability limiting component as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
(26 reference statements)
0
6
0
Order By: Relevance
“…As previously mentioned, filamentary, memristive VCM cells can be manufactured using different materials, being classified according to their switching mode, conductive path and switching mechanism. Different implementations of a HfO2-based memristor (TiN/HfO2/TiN or TiN/HfO2/Ti/ TiN) are described in [10,11,4,23] and a TaOx based memristor (Ta2O5/TaOx) proposed by Panasonic is described in [15,19,15]. The manufacturing process of memristive devices aims to create devices composed of three main parts, the Bottom Electrode (BE), the Transition Metal Oxide (TMO) and finally, the Top Electrode (TE).…”
Section: Manufacturing Process and Possible Defectsmentioning
confidence: 99%
See 1 more Smart Citation
“…As previously mentioned, filamentary, memristive VCM cells can be manufactured using different materials, being classified according to their switching mode, conductive path and switching mechanism. Different implementations of a HfO2-based memristor (TiN/HfO2/TiN or TiN/HfO2/Ti/ TiN) are described in [10,11,4,23] and a TaOx based memristor (Ta2O5/TaOx) proposed by Panasonic is described in [15,19,15]. The manufacturing process of memristive devices aims to create devices composed of three main parts, the Bottom Electrode (BE), the Transition Metal Oxide (TMO) and finally, the Top Electrode (TE).…”
Section: Manufacturing Process and Possible Defectsmentioning
confidence: 99%
“…A slightly different device form is the pillar cell, where the MIM layer stack is deposited as a whole and is finally etched into the desired shape. The BE and TE are contacted by vias [11]. Note that in this paper, the focus is laid on the crossbar cell design due to the possibility to build on every substrate, either a passive, planar disc or a CMOS-type substrate with contact pads reaching to the top surface [10].…”
Section: Manufacturing Process and Possible Defectsmentioning
confidence: 99%
“…More precisely, it was showed that for median resistances higher than the dispersion follows a lognormal distribution with median parameter T50=172kΩ and form factor =0.78. is the quantum conductance unit corresponding to the creation of a single conductive nanowire (28). Consequently, large compliance currents induce higher variability and lower  even at the first Set/Reset operation, making challenging the development of RRAM technology for low power applications.…”
Section: Window Margin Variabilitymentioning
confidence: 99%
“…Where R is the cell resistance,  the barrier height and α related to the width of the barrier, assuming a parabolic longitudinal potential. Those parameters refer to the QPC model (28). Resistance standard deviation fundamental limit is linked to the discreteness of the number of elements (vacancies/ atoms) participating to the conduction, and following a Poisson distribution.…”
Section: Window Margin Variabilitymentioning
confidence: 99%
“…Therefore, considering and improving the reliability of designs for CIM are crucial. For the VCM-ReRAM devices, cycle-to-cycle (C2C) and device-to-device (D2D) switching variabilites as well as read instabilities [5][6][7] might occur which can lead to a variation in the observed device resistance or in the switching process. This possibly degrades the device performance as data storage cell or in CIM computation.…”
Section: Introductionmentioning
confidence: 99%